Correlation of serum intact parathyroid hormone and alkaline phosphatase in diabetic chronic kidney disease stage 3 to 5 patients with mineral bone disorders - Ananna, Mehruba Alam; Haque, Wasim Md Mohosin Ul; Rahim, Muhammad Abdur; Chowdhury, Tufayel Ahmed; Samad, Tabassum; Billah, Md Mostarshid; Iqbal, Sarwar (IMC Journal of Medical Science, 2019)
Introduction: Chronic kidney disease (CKD) amongst diabetic patients is a worldwide public health problem. It is associated with cardiovascular disease and CKD mineral bone disorder (CKD-MBD). Cardiovascular and MBD are important contributors of morbidity and mortality in CKD patients. Serum intact parathyroid hormone (iPTH) and alkaline phosphatase (ALP) are two important markers to identify and mange CKD-MBD. This study was designed to evaluate the relationship between serum iPTH and alkaline phosphatase in diabetic CKD stages 3-5 patients with MBD. Methods: This cross-sectional study was conducted in BIRDEM General Hospital, Dhaka, Bangladesh from January 2013 to December 2014. Diabetic patients suffering from stage 3-5 CKD with MBD and not on dialysis, were consecutively and purposively included in this study. Along with base-line characteristics, clinical and laboratory data including serum alkaline phosphatase and iPTH levels were recorded for all patients. Data were analyzed by using SPSS version 20.0 and Pearson’s correlation test was applied to evaluate the relationship between iPTH and serum ALP. Results: Total patients were 306, of which 166 (54.2%) were males and 140 females (45.8%). Mean age of the study population was 56.5±11.3 years. Mean duration of diabetes mellitus (DM) and CKD were 12.8±7.6 and 2.9±1.7 years respectively. Among the study population, 49 (16.0%) were in CKD stage 3, 90 (29.4%) in stage 4 and rest 167 (54.6%) in stage 5. The mean HbA1c level did not differ significantly (p>0.05 by ANOVA) amongst CKD-MBD stage 3, 4 and 5 cases. Mean±SE values of glycated haemoglobin (HbAlc %), serum creatinine (mg/dl), urea (mg/dl), calcium (mg/dl), phosphate (mg/dl), ALP (U/L) and iPTH (pg/ml) of total study population were 7.77±0.12, 6.8±0.17, 141.1±4.33, 8.1±0.07, 5.2±0.11, 164.1±7.74 and 229.7±8.64 respectively. Out of total cases, serum ALP was raised in only 53.9% CKD-MBD cases compared to 76.8% for iPTH. Serum iPTH level was found elevated in 79.6%, 83.3% and 72.5% CKD-MBD stage 3, 4 and 5 cases respectively while in comparison, serum ALP was found raised in 44.8%, 54.4% and 56.2% cases respectively. On correlation analysis between serum iPTH and ALP, the r values observed were 0.074, 0.231 and 0.046 for stage 3, 4 and 5 CKD-MBD cases respectively. Conclusion: The results of current study showed that most diabetic stage 3-5 pre-dialysis CKD-MBD patients had raised serum iPTH. In comparison, significantly low number of cases had raised serum ALP. IMC J Med Sci 2018; 12(2): 80-85